DAMPAK DEFISIT UNSUR KALIMAT PADA FUNGSI PRAGMATIS TINDAK TUTUR ANAK DISABILITAS GANDA (Impact of Deficit Elements of Sentence there is a Pragmatic Function Speech Act of Children with Multiple Disabilities) - Rahayu Pujiastuti; Ira Eko Retnosari (SAWERIGADING, 2023)
The limitations of children with multiple disabilities lead to distinctiveness in the sentences produced and have an impact on the understanding of speech partners.  This study aims to describe the form of sentences in Indonesian children with multiple disabilities and their impact on pragmatic functioning. This qualitative descriptive research uses a longitudinal data collection method. The study subjects were three children with multiple disabilities who were severely deaf and slow to learn. Data in the form of utterances that inform the form of sentences of children with multiple disabilities and their impact on pragmatic functioning.  Data collection using observation and fishing is supported by field recording and recording.  The analysis uses sorting, reverse, and connecting techniques. The validity of the data uses triangulation of theories, methods, and sources. There are two results of this study. First, the sentences produced by children with multiple disabilities are holophrases sentences or one-word sentences.  Second, the deficit of sentence elements gives rise to misunderstandings because it can refer to some pragmatic function so that the speech partner often does not understand fully even though the child has replaced it with a gesture. Hearing and cognitive development limitations cause disabilities to accept and understand exposure, thus impacting the sentences produced.  Children with multiple disabilities experience cognitive developmental delays of 5;6–6;0. AbstrakKeterbatasan anak disabilitas ganda menyebabkan ke-khas-an pada kalimat yang diproduksi dan berdampak pada pemahaman mitra tutur. Tujuan penelitian ini untuk mendeskripsikan wujud kalimat bahasa Indonesia anak disabilitas ganda dan dampaknya pada fungsi pragmatis. Penelitian deskriptif kualitatif ini menggunakan metode pengumpulan data longitudinal. Subjek penelitian tiga anak disabilitas ganda yang menyandang tunarungu berat dan lamban belajar. Data berupa tuturan yang menginformasikan wujud kalimat anak disabilitas ganda dan dampaknya pada fungsi pragmatis. Pengumpulan data menggunakan pengamatan dan pemancingan didukung perekaman dan pencatatan lapangan. Penganalisisan menggunakan teknik pilah, balik, dan hubung. Keabsahan data menggunakan triangulasi teori, metode, dan sumber. Ada dua hasil penelitian ini. Pertama, kalimat yang dihasilkan anak disabilitas ganda berupa kalimat holofrase atau kalimat satu kata. Kedua, defisit unsur kalimat menimbulkan kesalahpahaman karena dapat merujuk pada beberapa fungsi pragmatis sehingga mitra tutur sering tidak memahami secara lengkap meskipun anak sudah mengganti dengan isyarat. Keterbatasan pendengaran dan perkembangan kognitif menyebabkan hambatan untuk menerima dan memahami pajanan sehingga berdampak pada kalimat yang diproduksi. Anak disabilitas ganda mengalami keterlambatan perkembangan kognitif 5;6–6;0.